EFFECT OF PASTEURISATION ON THE CONCENTRATIONS OF VITAMIN D COMPOUNDS IN DONOR BREAST MILK. Issue 9 (17th August 2016) - Gomes, Fabio; Shaw, Nick; Whitfield, Karen; Koorts, Pieter; McConachy, Helen; Hewavitharana, Amitha
Abstract : Aim: Breastmilk is considered the most important nutrient and source of supplementation for both term and preterm infants.1 It is composed of many important nutrients, including vitamin D.2 The content of this vitamin in breast milk is usually low, even for lactating mothers with adequate vitamin D status.2 3 Preterm infants are at the great risk of vitamin D deficiency due to decreased transplacental transfer.4 Premature infants are the main recipients of pasteurised donor human milk (PDHM), when their mothers are unable to provide their own. This study aims to evaluate the effect of pasteurisation on the concentrations of vitamin D compounds in donor breast milk. Method: A total of 16 participants, who donated breast milk to the RBWH milk bank, were recruited in this study. Milk samples were obtained pre- and post-Holder pasteurisation. Liquid chromatography tandem mass spectrometry (LC-MS/MS) was used to analyse the samples for vitamins D2 and D3 and 25-hydroxyvitamins D2 and D3 (25(OH)D2 and 25(OH)D3). The significance of differences in vitamin D concentrations between the two groups of milk samples was assessed using the Wilcoxon matched-pairs signed rank test, in which P<0.05 was considered significant. Results: Pasteurisation resulted in a significant reduction (P<0.05) in the content of D2, D3, 25(OH)D2 and 25(OH)D3, with P values of 0.0001 for all targeted analytes. The concentrations of the vitamin D analogues in non-pasteurised milk ranged from 3.6 to 5.0 pM (D2), 1.0 to 9.8 pM (D3), 1.4 to 2.1 pM (25(OH)D2) and 1.2 to 9.3 pM (25(OH)D3). The concentrations of the vitamin D analogues in post-pasteurised milk ranged from 3.0 to 4.0 pM (D2), 0.6 to 9.5 pM (D3), 1.2 to 1.7 pM (25(OH)D2) and 1.1 to 9.1 pM (25(OH)D3). Losses of vitamin D compounds resulting from the pasteurisation process ranged from 10% to 20%. Conclusion: Pasteurisation significantly affected the concentration of vitamin D compounds in pasteurised donor breast milk.